CURRICULUM DEVELOPMENT OF MULTICULTURAL-BASED ISLAMIC EDUCATION AS AN EFFORT TO WEAVER RELIGIOUS MODERATION VALUES IN INDONESIA - Abidin, Achmad Anwar; Murtadlo, Muhammad Ali (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2020)
Abstract: the discussion in this article refers to the development of a multicultural-based Islamic religious education curriculum as an effort to develop the values of religious moderation in Indonesia that have been implemented. The research method in this article is an observative research on educational institutions in Indonesia from the policy side of government and related educational institutions. The conclusion is as follows: 1). Multicultural-based Islamic religious education learning Model. In developing a multicultural learning model that must be blessed is a truly multicultural-laden learning activity. Learning activities are designed to provide a learning experience involving mental and physical processes through interaction between learners, learners with teachers, the environment, and other learning resources in order to achieve basic competencies. 2). Learning Media of Islamic religious education. Media can also be called tools while commonly used at this time is an audio visual aids, which means audiovisual aids are materials or tools used in the situation to help the writings and words spoken in the transmission of knowledge, attitudes, and ideas in the development of Islamic education be bases multicultural. 3). Sources of educational learning Islamic religion-based multicultural sources of Islamic values as a cornerstone of Islamic education The Foundation consists of the Qur'an and Sunnah Prophet Muhammad SAW that was developed with Ijtihad, Al Maslahah al murincorrectly, Istihsan, Qiyas and so on and from the source of learning it in the Islamic Religious education based multicultural developed with regard to the values of Islam Rahmatan li Al-"alamin that put forward the principles of Islamic Humanist , tolerant, democratic, and accommodating local cultures.